Kronična obstruktivna pljučna bolezen (KOPB) - Debeljak, Andrej (Medicinski razgledi, 2003)
The article presents the diagnosis, management, and prevention of chronic obstructive lung disease. It is written depending on the Global initiative forchronic obstructive lung disease conducted by US National heart, lung and blood institute and World health organisation. Initiative was accepted by Slovenian respiratory society. We presented systematically: definition, epidemiological data, risk factors, pathogenesis, pathology, pathogenesis and treatment of COPD. The importance of smoking cesseation, medical treatment andrehabilitation is stressed. The burden of COPD in Slovenia is shown.
Keywords: Bolezen, napredovanje; Lung Diseases, Obstructive; Diagnosis; Pljučne bolezni obstruktivne; Therapy; Bronhodilatatorji; Dejavniki tveganja; Prevention And Control; Kisik, vdihavanje, zdravljenje; Disease Progression; Risk Factors; Pljučni volumen, meritve; Spirometrija; Spirometry; Telesna vadba; Lung Volume Measurements; Bronchodilator Agents; pljučne bolezni; Exercise; kronična obstruktivna pljučna bolezen; Oxygen Inhalation Therapy; zdravljenje; preprečevanje; diagnostika